A teoria da emancipação em Karl Marx e Jürgen Habermas - Beltrame, Matheus Maria (2017)
The thesis The theory of emancipation in Karl Marx and Jürgen Habermas aims to understand the conceptual historical development of emancipation’s notion. The emergence of this concept occurs in the universe of Roman law and remain with this characteristic until the eighteenth century, in the Enlightenment movement, when it will receive new meanings. The emancipation’s concept is present in the Karl Marx and Jürgen Habermas’s thinking, from distinct categories, respectively, work and interaction, but within the same notion of Enlightenment rationality. Our hypothesis is that a relation of distinction between the competing thoughts of these authors is established, but that it will enable the understanding of the theory of the emancipation of both, arising from influences of the Enlightenment. To answer this problem we go through four stages: first, we approach the state of the art of emancipation’s concept; Second, we investigate the notion of human emancipation in Marx; Third, we analyze the emancipatory conception of Habermas and fourth, we approach a critique of the habermasian notion from contemporary philosophy.